Differential predictors of ART adherence among HIV-monoinfected versus HIV/HCV-coinfected individuals. Issue 8 (2nd August 2016) - Shuper, Paul A.; Joharchi, Narges; Irving, Hyacinth; Fletcher, David; Kovacs, Colin; Loutfy, Mona; Walmsley, Sharon L.; Wong, David K.H.; Rehm, Jürgen
ABSTRACT: Although adherence is an important key to the efficacy of antiretroviral therapy (ART), many people living with HIV (PLWH) fail to maintain optimal levels of ART adherence over time. PLWH with the added burden of Hepatitis C virus (HCV) coinfection possess unique challenges that potentially impact their motivation and ability to adhere to ART. The present investigation sought to (1) compare ART adherence levels among a sample of HIV/HCV-coinfected versus HIV-monoinfected patients, and (2) identify whether ART-related clinical and psychosocial correlates differ by HCV status. PLWH receiving ART ( N  = 215: 105 HIV/HCV-coinfected, 110 HIV-monoinfected) completed a comprehensive survey assessing ART adherence and its potential correlates. Medical chart extraction identified clinical factors, including liver enzymes. Results demonstrated that ART adherence did not differ by HCV status, with 83.7% of coinfected patients and 82.4% of monoinfected patients reporting optimal (i.e., ≥95%) adherence during a four-day recall period ( p  = .809). Multivariable logistic regression demonstrated that regardless of HCV status, optimal ART adherence was associated with experiencing fewer adherence-related behavioral skills barriers (AOR = 0.56; 95%CI = 0.43–0.73), lower likelihood of problematic drinking (AOR = 0.15; 95%CI = 0.04–0.67), and lower likelihood of methamphetamine use (AOR = 0.14; 95%CI = 0.03–0.69). However, among HIV/HCV-coinfected patients, optimal adherence was additionally associated with experiencing fewer ART adherence-related motivational barriers (AOR = 0.23; 95%CI = 0.08–0.62) and lower likelihood of depression (AOR = 0.06; 95%CI = 0.00–0.84). Findings suggest that although HIV/HCV-coinfected patients may face additional, distinct barriers to ART adherence, levels of adherence commensurate with those demonstrated by HIV-monoinfected patients might be achievable if these barriers are addressed.